Dysbiosis of the gut microbiota and its effect on α-synuclein and prion protein misfolding: consequences for neurodegeneration - Mahbub, Nasir Uddin; Islam, Md Minarul; Hong, Seong-Tshool; Chung, Hea-Jong (Frontiers in Cellular and Infection Microbiology, 2024)
Abnormal behavior of α-synuclein and prion proteins is the hallmark of Parkinson’s disease (PD) and prion illnesses, respectively, being complex neurological disorders. A primary cause of protein aggregation, brain injury, and cognitive loss in prion illnesses is the misfolding of normal cellular prion proteins (PrPC) into an infectious form (PrPSc). Aggregation of α-synuclein causes disruptions in cellular processes in Parkinson’s disease (PD), leading to loss of dopamine-producing neurons and motor symptoms. Alteration in the composition or activity of gut microbes may weaken the intestinal barrier and make it possible for prions to go from the gut to the brain. The gut-brain axis is linked to neuroinflammation; the metabolites produced by the gut microbiota affect the aggregation of α-synuclein, regulate inflammation and immunological responses, and may influence the course of the disease and neurotoxicity of proteins, even if their primary targets are distinct proteins. This thorough analysis explores the complex interactions that exist between the gut microbiota and neurodegenerative illnesses, particularly Parkinson’s disease (PD) and prion disorders. The involvement of the gut microbiota, a complex collection of bacteria, archaea, fungi, viruses etc., in various neurological illnesses is becoming increasingly recognized. The gut microbiome influences neuroinflammation, neurotransmitter synthesis, mitochondrial function, and intestinal barrier integrity through the gut-brain axis, which contributes to the development and progression of disease. The review delves into the molecular mechanisms that underlie these relationships, emphasizing the effects of microbial metabolites such as bacterial lipopolysaccharides (LPS), and short-chain fatty acids (SCFAs) in regulating brain functioning. Additionally, it looks at how environmental influences and dietary decisions affect the gut microbiome and whether they could be risk factors for neurodegenerative illnesses. This study concludes by highlighting the critical role that the gut microbiota plays in the development of Parkinson’s disease (PD) and prion disease. It also provides a promising direction for future research and possible treatment approaches. People afflicted by these difficult ailments may find hope in new preventive and therapeutic approaches if the role of the gut microbiota in these diseases is better understood.